Short-term clinical outcome after acute symptomatic pulmonary embolism - Conget, Francisco; Otero, Remedios; Jiménez, David; Martí, David; Escobar, Carlos; Rodríguez, Consolación; Uresandi, Fernando; Cabezudo, Miguel Angel; Nauffal, Dolores; Oribe, Mikel; Yusen, Roger (Thrombosis and Haemostasis, 2008)
Though studies have identified clinical variables that predict adverse events in patients with acute pulmonary embolism (PE), they have typically not differentiated short-term from long-term predictors.This multicenter prospective cohort study included consecutive outpatients with objectively confirmed symptomatic acute PE.We analyzed the incidence and time course of death, venous thromboembolism (VTE) recurrence, and major bleeding, and we compared event rates during short-term (first week) and long-term (3 months) follow-up after the diagnosis of PE.We also assessed risk factors for short-term mortality. During the first three months after diagnosis of PE, 142 of 1,338 (10.6%) patients died.Thirty-six deaths (2.7%) occurred during the first week after diagnosis of PE,and 61.1% of these were due to PE.Thirty-eight patients (2.8%) had recurrent VTE during the three-month follow-up, though none of the recurrences occurred during the first week after diagnosis of PE. During the three-month follow-up, major bleeding occurred in 48 patients (3.6%). Twenty-one (1.6%) major bleeds occurred during the first week of follow-up,and nine of these were fatal. Short-term mortality was significantly increased in patients who initially presented with systolic arterial hypotension (odds ratio [OR] 3.35; 95% CI, 1.51-5.41) or immobilization due to a medical illness (OR 2.89; 95% confidence interval [CI], 1.31-6.39).In con-clusion,during the first week after the diagnosis of PE, death and major bleeding occur more frequently than recurrent VTE. Patients with systolic arterial hypotension and immobilization at the time of PE diagnosis had an increased isk of short-term mortality.
Keywords: Pulmonary embolism; prognosis; adverse events